Search for dark matter produced in association with a Higgs boson decaying to bb [bar] using 36 fb−1 of pp collisions at √s = 13 TeV with the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Bolz, Arthur; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; et al. (Physical review letters, 2017)
Several extensions of the standard model predict associated production of dark-matter particles with a Higgs boson. Such processes are searched for in final states with missing transverse momentum and a Higgs boson decaying to a b¯b pair with the ATLAS detector using 36.1 fb−1 of pp collisions at a center-of-mass energy of 13 TeV at the LHC. The observed data are in agreement with the standard model predictions and limits are placed on the associated production of dark-matter particles and a Higgs boson.
ATLAS Collaboration: M. Aaboud, C.F. Anders, V. Andrei, C. Antel, A.E. Baas, A.E. Bolz, O. Brandt, J.I. Djuvsland, M. Dunford, D.E. Ferreira de Lima, S. Franchino, M.P. Geisler, M. Giulini, P. Hanke, J. Jongmanns, E.-E. Kluge, M. Kolb, A. Kugel, V.S. Lang, M. Lisovyi, H. Meyer Zu Theenhausen, D.I. Narrias Villar, M. Sahinsoy, S. Schaetzel, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, M. Wessels [und weitere]
Im Titel ist "-1" hochgestellt
Gesehen am 29.03.2018